Ukusetshenziswa kolimi lwesiZulu njengesu lokuthuthukisa ulwazi lokubala kunzikandaweni wemfundo yasezikhungweni zokuhlunyeleliswa kwezimilo - Mbatha, Siphelele; Khohliso, Xolani; Nsele, Sanele (Journal for Language Teaching, 2025)
ENGLISH TITLE: The use of isiZulu language as the strategy towards developing numerical literacy in correctional centre classrooms The advent of democracy in South Africa introduced the plethora of transformations in the Correctional Services framework. Amongst these transformations is the infusion of offender education component, economic development through rehabilitation, and the advancement of social cohesion through offender rehabilitation. These transformations are, even though not apparently so, intertwined and coordinated for the purpose of offender holistic rehabilitation. For example, vision for the Department of Correctional Services includes (but it is not limited to) offering formal education to offenders so that they will be pro-active in developing the South African economy and further attain the skill(s) of living in harmony with fellow South African citizens. Preceding research, which sought to reveal offender rehabilitation strategies has centralised and defined offender education as the resource for competing the offender rehabilitation process. However, it is paramount to note that offender formal education has been discussed at a very generic lens, without focusing on the role played by each learning area in completing the rehabilitation process. Furthermore, the language used in the learning, teaching and assessment of offenders has been overlooked, particularily in scholarship that focuses on offender development and care. In this paper, researchers sought to examine the teaching, learning and assesment of quantitative literacy and the impact thereof of using isiZulu language in correctional centre classrooms. From the pragmatic epistemological stance, researchers collected both qualitative and quantitative data through pre-tests, post-tests and semi-structured interviews to address the research question: How can the use of isiZulu as the Language of Learning and Teaching be associated with the developement of quantitative literacy in correctional centre classrooms? The intellectual piece was framed within the QUANT-QUAL explanatory sequential mixed methods design. The Andragogic theoretical ideas were used as lens upon which the study was underpinned. The findings reveal the statistically significant impact of isiZulu in the development of quantitative literacy. Amongst the findings which were inferred from the study is the significant role of isiZulu language in the development of mathematics deeper conceptual understanding. The study further revealed the two-fold role of language use in correctional centre classrooms (that is, the development of mathematics register and the development of isiZulu as a language). IsiZulu language was further distinguished as the tool towards the decolonization of the mathematics curriculum in correctional centre classrooms. Finally, the researchers propose the use of learners’ Home Language in adult correctional centre classrooms. Iqoqa Imfundo isetshenziswa ukuphelelisa ukuhlunyeleliswa kwezimilo. Imfundo yeziboshwa iye yadingidwa akwangahlolisiswa iqhaza elibanjwa isifundo ngasinye ekuhlumeleliseni izimilo. Nolimi olusetshenziswa lapho kufundwa, kufundiswa noma kuhlolwa iziboshwa luye lwashaywa indiva. Kuleli phepha, abacwaningi bebehlola umthelela wokusetshenziswa kolimi lwesiZulu lapho kufundwa, kufundiswa futhi kuhlolwa izibalo ezikhungweni zokuhlunyeleliswa kwezimilo. Kusetshenziswe indlelakubuka yokubheka ukwenzeka kwesenzeko simbe. Kuqoqwe ulwazi lobunjalo botho nolobungako botho ngamathuluzi amathathu; isivivinyo sangaphambi kocwaningo, isivivinyo sangemva kocwaningo kanye nenhlolovo esakuhleleka. Lo msebenzi uye wamiswa ngokomdwebomumo wocwaningo oluxube ubungako botho nobunjalo botho, kuqaliswa ngolwazi lobungako botho, kulandeliswa ngolwazi lobunjalo botho. Insizakuhlaziya ebheka isu lokufundiswa kwabantu abadala iye yasetshenziswa lapho kuhlaziywa ulwazi oluveze ukuthi ulimi lwesiZulu luthuthukisa ulwazi lokubala ngobungako obucacile uma luqhathaniswa nesiNgisi. Kuhlaluke iqhaza elidlalwa ulimi lwesiZulu ekuthuthukiseni ulwazi lokubala. Ulimi lwesiZulu luphinde lwahlonzwa njengethuluzi elinqanda ukuqonelwa kohlelo lwesifundo sezibalo. Abacwaningi baphakamisa ukusetshenziswa koLimi lwaseKhaya njengoLimi lokuFunda nokuFundisa konzikandaweni bokufundela ezikhungweni zokuhlunyeleliswa kwezimilo.